Integrasi Computational Thinking dalam Pembelajaran Matematika di Madrasah Ibtidaiyah - Safik, Moh. (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2022)
This research aims to investigate the relevance and stages of integrating Computational Thinking in mathematics learning at Madrasah Ibtidaiyah (Islamic primary schools). The approach used is qualitative-descriptive. The research findings indicate that Computational Thinking in mathematics learning has significant relevance in developing critical thinking skills, and problem-solving abilities, and preparing students to face challenges in the digital era. Computational thinking helps students connect mathematical concepts to real-world contexts, motivates learning, and establishes a relationship between mathematics and everyday life. Meanwhile, the integration of Computational Thinking in mathematics learning at Islamic primary schools requires a holistic and sustainable approach to ensure effective understanding and implementation.